Trilateral development cooperation with "New Donors" - Tilman Altenburg; Jochen Weikert (Deutsches Institut für Entwicklungspolitik (DIE), 2007)
Many traditional aid recipient countries have recently also become donors of development aid. In particular, anchor countries such as China, India, Brazil, Mexico, South Africa, and Thailand are increasingly providing aid programs for needier developing countries. In some cases, however, this masks trade and political interests to a greater extent than in the case of donors belonging to the Organisation for Economic Co-operation and Development (OECD).Various among these New Donors direct inquiries to OECD countries for carrying out joint development projects in third countries or for receiving support in building up their own donor institutions. OECD donors have a clear interest in integrating these New Donors into a democratic and multilateral world order. From this point of view, the assumption of international responsibility displayed by the New Donors through their engagement can only be welcomed. On the other hand, this engagement should also be aligned with the international donor consensus, especially as set forth in the MDG Agenda and the Paris Declaration of the Development Assistance Committee (DAC ) of the OECD. This is currently not the case with all New Donors. Particularly China – which, along with some of the Gulf States, is by far the most important donor outside the DAC – is often criticised both for its unconditional support of countries with bad governance records and for its tied aid.Then how should established DAC donors react to inquiries for trilateral development cooperation made by the New Donors? New Donors who already align their policies with the consensus principles should be invited to joint projects in third countries – provided that the required management costs and efforts remain within reasonable limits for all concerned. An important aim here is to convey good donor standards and experience to the emerging donor institutions.In order to also engage the other New Donors for DAC principles, open dialogue should be upheld and indirect cooperation should be offered.
Keywords: 330